Smartphone applications for melanoma detection by community, patient and generalist clinician users: a review. (1st June 2015) - Kassianos, A.P.; Emery, J.D.; Murchie, P.; Walter, F.M.
Summary: Smartphone health applications ('apps') are widely available but experts remain cautious about their utility and safety. We reviewed currently available apps for the detection of melanoma (July 2014), aimed at general community, patient and generalist clinician users. A proforma was used to extract and assess each app that met the inclusion criteria, and we undertook content analysis to evaluate their content and the evidence applied in their development. Thirty‐nine apps were identified with the majority available only for Apple users. Over half ( n = 22) provided information or education about melanoma, ultraviolet radiation exposure prevention advice, and skin self‐examination strategies, mainly using the ABCDE (A, Asymmetry; B, Border; C, Colour; D, Diameter; E, Evolving) method. Half ( n = 19) helped users take and store images of their skin lesions either for review by a dermatologist or for self‐monitoring to identify change, an important predictor of melanoma; a similar number ( n = 18) used reminders to help users monitor their skin lesions. A few ( n = 9) offered expert review of images. Four apps provided a risk assessment to patients about the probability that a lesion was malignant or benign, and one app calculated users' future risk of melanoma. None of the apps appeared to have been validated for diagnostic accuracy or utility using established research methods. Smartphone apps for detecting melanoma by nonspecialist users have a range of functions including information, education, classification, risk assessment and monitoring change. Despite their potential usefulness, and while clinicians may choose to use apps that provide information to educate their patients, apps for melanoma detection require further validation of their utility and safety.